Elementary School Teachers’ Conception of E-learning and Blended Learning - Syarifah, Mufarrahatus; Handayani, Hany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The developments of school infrastructure that provides and involves computersin learning encourage teachers to adapt the use of these advanced technologies. The intended form of adaptation is through e-learning. Questionnaires were given to 43 elementary school teachers, who were able to operate computers, randomly selected to describe e-learning concept that they understood and applied. Although the majority of them mention e-learning specifically as learning involving computers in their implementation, and assuming they have implemented e-learning, they basically apply blended learning. Computers were used as a complementary medium, not the main. Through the results of the survey conducted, we discussed a gap between the perceptions of elementaryschool teachers believed with the actual concept of e-learning. Through the discussion, we also obtained a picture of how the actual application of e-learning by teachers is blended learning. Suggestions on the urgency of implementing e-learning in elementary school are also included.